A Critical LRRK at the Synapse? The Neurobiological Function and Pathophysiological Dysfunction of LRRK2 - Kuhlmann, Naila; Milnerwood, Austen J. (Frontiers in Molecular Neuroscience, 2020)
Since the discovery of LRRK2 mutations causal to Parkinson’s disease (PD) in the early 2000s, the LRRK2 protein has been implicated in a plethora of cellular processes in which pathogenesis could occur, yet its physiological function remains elusive. The development of genetic models of LRRK2 PD has helped identify the etiological and pathophysiological underpinnings of the disease, and may identify early points of intervention. An important role for LRRK2 in synaptic function has emerged in recent years, which links LRRK2 to other genetic forms of PD, most notably those caused by mutations in the synaptic protein α-synuclein. This point of convergence may provide useful clues as to what drives dysfunction in the basal ganglia circuitry and eventual death of substantia nigra (SN) neurons. Here, we discuss the evolution and current state of the literature placing LRRK2 at the synapse, through the lens of knock-out, overexpression, and knock-in animal models. We hope that a deeper understanding of LRRK2 neurobiology, at the synapse and beyond, will aid the eventual development of neuroprotective interventions for PD, and the advancement of useful treatments in the interim.